KitÄb Seribu MasÄâ€™il Salinan dari Banten: Sebuah Konstruksi Sejarah Proses Islamisasi Nusantara - shoheh, muhamad; Sugito, Muhammad Shofin (Jurnal Lektur Keagamaan, 2019)
This brief paper discusses one of the classical literary texts of Islamic Nusantara entitledÂ Kitab Seribu MasalahÂ (the book of a thousand problems). This study uses a philological and textual approach to reveal the relationship and linkage between text and context, which then leads to efforts to produce interpretations related to the history of the Islamization process in the archipelago. This research is conducted to answer three problems, namely: How the KSM manuscript description, what is the content of the text, and how the context behind the birth of the work.From the idea side,Â Kitab Seribu MasalahÂ contains dialogue between two people: First, the figure of Muhammad saw. in the manuscript is described as an end-time prophet of God's messenger, who calls to believe in Him. He is believed to have abundant knowledge from Allah swt., so that it can answer various problems that are considered and faced by Humans. Second, the figure of Abdullah ibn As-Salam of the Tribe of Thamud illustrated as a clever Jewish clergyman, very pious to the contents of the Torah, Gospel, Zabur and earlier books. He is so trustworthy and has a large fanatic followers of up to seven hundred people. The dialogue at least explores the problem of the relationship between God and His Messenger, regarding cosmological issues, about eschatology, testing the intelligence of the end-time prophet, the puzzle, the meaning of numbers, and others.Keywords:Â Kitab Seribu Masalah, Hikayat, 'Abdullah bin Salam, Islamization of the ArchipelagoÂ Tulisan singkat ini membahas salah satu teks klasik Islam Nusantara yang berjudulÂ Kitab Seribu Masalah. Penelitian ini menggunakan pendeÂkatan filologis dan tekstologis untuk mengungkap hubungan antara teks dan konteks, yang kemudian bermuara pada usaha-usaha memproduksi interpretasi-interpretasi terkait sejarah proses Islamisasi di Nusantara. Penelitian ini dilakukan untuk menjawab masalah kandungan isi naskahÂ KSM, dan konteks yang melatarbelakangi lahirnya, serta kaitannya dengan proses Islamisasi Nusantara.Penelitian ini berkesimpulan bahwa terdapat 13 buah naskah yang berjudulÂ KitÄb Seribu MasÄâ€™ilÂ atauÂ Hikayat Seribu Masalah.Â Dari tiga belas naskah tersebut, 9 naskah ada di PNRI Jakarta dan 4 naskah ada di Universitas Leiden, Belanda. Ketiga belas naskah yang dimaksud adalah naskah ML 19, ML 59, ML200, ML 442, W 82, W 83, W 84, W 85, W 86, KL.26, 6064 D, OPH 72, dan Cod. Or. 1960. Setelah melakukan perbanÂdingan akhirnya peneliti memilih naskah ML 19 sebagai obyek untuk dilaÂkukan penyuntingan dan edisi kritis.Dari sisi ide,Â KitÄbÂ Seribu MasalahÂ berisi dialog antara Nabi Muhammad saw. dan Abdullah bin Salam. Abdullah bin Salam adalah seoÂrang tokoh dari Suku Tsamud yang diilustrasikan sebagai seorang pendeta Yahudi yang cerdik-pandai,Â alimÂ akan isi Taurat, Injil, Zabur dan kitab-kitab terdahulu. Ia begitu dipercaya dan mempunyai banyak pengikut fanatik hingga lebih dari tujuh ratus orang. Dialog tersebut berisi masalah relasi Allah dan Rasul-Nya, kosmologis, eskatologis, ujian kecerdasan Nabi, teka-teki, arti bilangan, dan lain-lain.Kata Kunci:Â KitÄb Seribu MasÄâ€™il,Â Hikayat, â€˜Abdullah bin Salam, Islamisasi Nusantara